Հովհան Օձնեցու փիլիսոփայական և կառավարչական հայացքները (Հովհան Օձնեցու գահակալության 1300-ամյակի առթիվ) - Յուրի Սուվարյան; Վալերի Միրզոյան (ՀՀ ԳԱԱ հրատ.)
Иоанн Философ Одзнеци занимает достойное место в армянской истории не только как выдающийся глава церкви, святой, за свои великие деяния канонизированный еще при жизни, но и как одна из вершин теоретической мысли.Hovhan Philosopher Odznetsi takes his rightful place in Armenian history not only as an outstanding head of the church, as a saint, for his great deeds canonized during his lifetime, but also as one of the vertices of theoretical thought.
Keywords: History; Biography; B Philosophy; Psychology; Religion; Auxiliary Sciences of History; Medieval History; B Philosophy; D History